Long-Term Sertraline Intake Reverses the Behavioral Changes Induced by Prenatal Stress in Rats in a Sex-Dependent Way - Pereira-Figueiredo, Inês; Castellano, Orlando; Riolobos, Adelaida S.; Ferreira-Dias, Graça; López, Dolores E.; Sancho, Consuelo (Frontiers in Behavioral Neuroscience, 2017)
Early life stress is a major factor underlying the vulnerability to respond to stressful events later in life. The present study attempted to evaluate the role of prenatal stress affecting the development of stress-related disorders and their reversion by postnatal exposure to Sertraline, a front-line medication for PTSD in humans. To achieve this, adult male and female prenatally stressed (PS) or unstressed (Controls) offspring rats, following oral chronic treatment with Sertraline (5 mg/kg/day) (from 1 month to 4 months old), or not, were studied prior to and after a traumatic event. First, anxiety-like behavior during the prepulse inhibition (PPI) test, a modulation of the startle reflex, was examined in all animals. Subsequently, the animals were subjected to a session of mild inescapable footshocks (IS) (0.35 mA, 5s) in a shuttle box that was followed by four days of situational reminders in the aversive context. Prior to the footshocks no effects of PS or Sertraline were shown, and no changes in PPI and the habituation to the shuttle box were found. After them, PS led animals to exhibit behavioral alterations. When compared to the Controls, PS animals of both sexes displayed less rearing activity in the aversive environment. PS males responded less to footshock delivery and, in most of the animals, fear extinction was impaired. Moreover, the early postnatal exposure to Sertraline lessened the behavioral impact of PS in females, while in males it had no effect. Current results extend previous data from our laboratory, showing that PS heightened vulnerability to stress later on, and that Sertraline acts differently in males and females.